A review of thematic growth of International Journal of Education and Development using ICT - Agbo, Friday Joseph; Olaleye, Sunday Adewale; Sanusi, Ismaila Temitayo; Dada, Oluwaseun Alexander (International journal of education and development using information and communication technology, 2021)
The growth in education, research, and development in developing economies cannot be compared with their developed counterparts. Information and Communication Technologies (ICTs), which have played a key role in nations' socio-economic development, can leverage developing economies. The International Journal of Education and Development using Information and Communication Technology (IJEDICT) emerged to promote research and development using ICT in developing nations. The emergence has, over the years, churned out significant scientific publications. This review intends to commemorate the late IJEDICT founding editor and investigate the contribution of academic papers published in the journal to develop education using ICT in developing countries and the thematic growth of the publication forum. The paper presents a bibliometric content analysis of 692 studies published in IJEDICT from inception, 2005 until January 2021. Findings from this review suggest useful implications for researchers, ICT managers, institutions, policymakers, and nations.